Geometric and Electronic Properties of Li2GeO3 - Khuong Dien, Vo; Thi Han, Nguyen; Nguyen, Thi Dieu Hien; Huynh, Thi My Duyen; Pham, Hai Duong; Lin, Ming-Fa (Frontiers in Materials, 2020)
The 3D ternary Li2GeO3 compound, which could serve as the electrolyte material in Li+-based batteries, exhibits an unusual lattice symmetry (orthorhombic crystal), band structure, charge density distribution and density of states. The essential properties are fully explored through the first-principles method. In the delicate calculations and analyses, the main features of atom-dominated electronic energy spectrum, space-charge distribution, and atom-/orbital-projected density of states are sufficient to identify the critical multi-orbital hybridizations of the chemical bonds: 2s-(2px, 2py, 2pz) and (4s, 4px, 4py, 4pz)-(2s, 2px, 2py, 2pz), respectively, for Li-O and Ge-O. This system possesses a large indirect gap of Eg=3.77 eV. There exist a lot of significant covalent bonds, with an obvious non-uniformity and anisotropy. In addition, spin-dependent magnetic configurations are completely absent. The theoretical framework could be developed to investigate the important features of anode and cathode materials related to lithium oxide compounds.